Strategi Representasi Eksternal Dalam Meningkatkan Keterampilan Kognitif Materi Hukum Newton Gerak Lurus - Hermawan, Sapto; Parlindungan Sinaga; Hikmat (Jurnal Pendidikan Nusantara, 2022)
External Representation is a learning strategy that is applied to convey the subject matter of teaching to students by using various modes of representation. The mode of representation consists of verbal representations, images, graphics, and mathematics. The application of the RE approach because learners experience learning obstacles to be able to understand newton's law of straight motion that is only conveyed verbally and mathematically. The purpose of this research is to train and improve students' cognitive skills in the domains of C1 (remembering), C2 (understanding), C3 (applying), and C4 (analyzing) in learning Physics. The research method used is a quasi-experimental design with a non-equivalent control group design. The subjects of this study were selected by purposive sampling. The students of class X Mathematics and Natural Sciences in a high school in West Bandung regency were 30 students in the experimental class and 30 students in the control class. Measurement of cognitive skills using multiple choice instruments on pre-test and post-test. Analysis to see the increase in students' cognitive skills using normalized gain analysis. The results obtained that the experimental class students have increased to the moderate category with a <g>= 0.41 and students in the control class have a moderate category with a value of <g>= 0.36 from each cognitive domain skill that is trained.